NEGOSIASI IDENTITAS PRIBUMI DAN BELANDA DALAM SASTRA POSKOLONIAL INDONESIA KONTEMPORER - Yusri Fajar (Faculty of Humanities, Jember University, 2011)
There are few postcolonial novels which narrate identity negotiation between Indonesians and Dutch people comprehensively since Pramoedya Ananta Toer wrote his phenomenal postcolonial novels quartet Buru. However, some contemporary Indonesian short stories highlight identity negotiation particularly in the era during which a lot of Indonesian students and immigrants live in the Netherlands, the former colonizer of Indonesia. This translocation indicates the deconstruction of the centre by the former colonized people from the place called periphery (colony). The movement of the former colonized Indonesian people to Netherlands, as a consequence, brings about identity negotiation in the metropolitan centre and creates what is called by Homi Bhabha in-between space. The identity of the Indonesian characters in those contemporary Indonesian literary works is constructed by the Dutch. Conversely, the identity of the Dutch is also stereotyped by the Indonesians. The relations between the Indonesians and Dutch people in the past, during the colonial period, to some extent engulfs that construction. Keywords: identity, postcolonial studies, the Self, the Other